The Highly Collimated Radio Jet of HH 80-81: Structure and Nonthermal Emission - Rodríguez Kamenetzky, Adriana Raquel (2017)
Radio emission from protostellar jets is usually dominated by free-free emission from thermal electrons. However, in some cases, it has been proposed that nonthermal emission could also be present. This additional contribution from nonthermal emission has been inferred through negative spectral indices at centimeter wavelengths in some regions of the radio jets. In the case of HH 80-81, one of the most powerful protostellar jets known, linearly polarized emission has also been detected, revealing that the nonthermal emission is of synchrotron nature from a population of relativistic particles in the jet. This result implies that an acceleration mechanism should be taking place in some parts of the jet. Here, we present new high sensitivity and high angular resolution radio observations at several wavelengths (in the 3-20 cm range) of the HH 80-81 radio jet. These new observations represent an improvement in sensitivity and angular resolution by a factor of ∼10 with respect to previous observations. This allows us to resolve the morphology of the radio jet and to study the different emission mechanisms involved through spectral index maps. We conclude that synchrotron emission in this jet arises from an extended component detected at low frequencies and from the termination points of the jet, where strong shocks against the ambient medium can produce efficient particle acceleration.